2022
DOI: 10.1002/ptr.7481
|View full text |Cite
|
Sign up to set email alerts
|

Psoralidin protects against cerebral hypoxia/reoxygenation injury: Role of GAS6/Axl signaling

Abstract: Psoralidin (PSO) is a natural phenolic coumarin extracted from the seeds of Psoralea corylifolia L. Growing preclinical evidence indicates that PSO has anti‐inflammatory, anti‐vitiligo, anti‐bacterial, and anti‐viral effects. Growth arrest‐specific gene 6 (GAS6) and its receptor, Axl, modulate cellular oxidative stress, apoptosis, survival, proliferation, migration, and mitogenesis. Notably, the neuroprotective role of the GAS6/Axl axis has been identified in previous studies. We hypothesize that PSO ameliorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, the role of the Hbegf-Erbb4 and Hbegf-Egfr ligand-receptor pairs in oxidative stress following SCI remains unexplored. Studies have also shown that activation of the GAS6/Axl-AMPK signaling pathway can protect against H2O2-induced oxidative stress, improving oxidative stress, cell apoptosis, and mitochondrial function [33,34] . Therefore, the GAS signaling pathway and the associated ligand-receptor pair Gas-Axl, which mediate cell communication in this study, may have a regulatory role in mitigating oxidative stress post-SCI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the Hbegf-Erbb4 and Hbegf-Egfr ligand-receptor pairs in oxidative stress following SCI remains unexplored. Studies have also shown that activation of the GAS6/Axl-AMPK signaling pathway can protect against H2O2-induced oxidative stress, improving oxidative stress, cell apoptosis, and mitochondrial function [33,34] . Therefore, the GAS signaling pathway and the associated ligand-receptor pair Gas-Axl, which mediate cell communication in this study, may have a regulatory role in mitigating oxidative stress post-SCI.…”
Section: Discussionmentioning
confidence: 99%
“…LDH release in the culture medium was determined using a commercially available kit according to the manufacturer's protocol (Nanjing Jiancheng Bioengineering Institute). For measurement of ROS production (Beyotime Biotechnology, Shanghai, China), please refer to Lei et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Protein expression was assessed using western blot analysis following established protocols (Lei et al, 2022). The antibody information used during the operation is shown in Supporting Information: Table S1.…”
Section: Western Blot Analysismentioning
confidence: 99%